2015
DOI: 10.1016/j.solener.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

New device for the simultaneous measurement of diffuse solar irradiance on several azimuth and tilting angles

Abstract: A device is proposed for the measurement of diffuse solar irradiance on tilted surfaces pointing-to as well as fixed on the equatorial direction. Most commercial devices are not designed for this purpose. Here, we present a specific design for a system based on a single multi-lobe shadow-ring that allows us to measure diffuse irradiance with several tilted pyranometers -from 60 to 90 degrees from the horizontal plane -and on different azimuth angles. This first prototype allows us to measure in the four cardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…They revealed that the function obtained for PSP pyranometers reduced the uncertainties in the radiation measurements. Martin et al [16] proposed a new device that allows for the simultaneous measurement of diffuse solar radiation along the azimuthal and tilt angles. They pointed out that not many commercial instruments were designed for this purpose and offered a specific design based on a single multi-lobe shadow-ring that was capable of measuring diffuse solar radiation on normal surfaces at 60-90 ˚C and along various azimuthal angles by a few tilted pyranometers.…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that the function obtained for PSP pyranometers reduced the uncertainties in the radiation measurements. Martin et al [16] proposed a new device that allows for the simultaneous measurement of diffuse solar radiation along the azimuthal and tilt angles. They pointed out that not many commercial instruments were designed for this purpose and offered a specific design based on a single multi-lobe shadow-ring that was capable of measuring diffuse solar radiation on normal surfaces at 60-90 ˚C and along various azimuthal angles by a few tilted pyranometers.…”
Section: Introductionmentioning
confidence: 99%
“…Muy pocas estaciones radiométricas realizan la medición de irradiancia difusa sobre plano inclinado en orientaciones distintas de la dirección Ecuatorial (Sur en este caso). En este sentido hemos desarrollado un prototipo [14] que, basado en los sistemas de medición de radiación difusa mediante anillo de sombreamiento, es capaz de realizar dicha medición simultáneamente sobre cuatro sensores ubicados en cuatro direcciones ortogonales y con la posibilidad de modificar el ángulo de inclinación de forma independiente entre 60 y 90 grados con la vertical. Dicho dispositivo puede observarse en la figura 2.c.…”
Section: Estación Swift0001unclassified